Nieinwazyjne badania in situ wybranych obrazów z kolekcji malarstwa i pasteli autorstwa Meli Muter za pomocą tomografii optycznej OCT - Iwanicka, Magdalena; Cybulska, Katarzyna A.; Sylwestrzak, Marcin (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2012)
Optical Coherence Tomography is a non-contact and non-invasive technique of depth-resolved structural imaging within media scattering and/or absorbing nearinfrared light moderately. It utilizes a concept of low-coherence interferometry and thus light sources must be characterized by low temporal (to ensure high axial resolution) and high spatial (to ensure high sensitivity) coherence. The instrument used in this study has 4 μm axial resolution and over 100 dB sensitivity. The modular construction based on fiber optics makes it fairly easy transportable and not requiring optical table mounting. The system’s portability together with fast and straightforward data acquisition, makes OCT especially well suited for quick in situ evaluation of large museum collections of paintings. A vast collection of seventy-one oil paintings and over one hundred drawings, watercolours, and graphics by Mela Muter (Maria Melania Mutermilch, 1876, Warsaw – 1967, Paris), gathered by Bolesław and Lina Nawrocki, is now on deposit to the Nicolaus Copernicus University Museum in Toruń. Artistically active in the first half of the twentieth century within the École de Paris, Mela Muter became recognized mostly for the portraits depicting socialites of the time, as well as images of motherhood, children and old people. The collection brings specific conservation problems. Since the works were mostly acquired from Muter herself, the attribution is not in question. Nevertheless, the majority of paintings bear signs of extent conservation treatment and/ or alterations performed by the artist in her late years, possibly including adding signatures. The aim of the survey of the group of nine Mela Muter’s paintings and two pastels was to define the conservation issues as well as to indicate the objects and areas for further examination with various analytical techniques. In result, the evaluation of secondary layers (varnishes and putties) was performed for seven paintings. The structure of the paint layer in the area of the signature was analyzed in three paintings. Finally, in case of two pastel paintings, the safety of pigment layer (its distance to the glass) was assessed.